Gambaran Persiapan Pelaksanaan Patient Safety Di Ruang IBS Rumah Sakit X - Azizah, Wafa Nur; Suandika, Made; Sukmaningtyas, Wilis (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Patient safety is the most important global issue today, with the highest number of reported claims for medical errors occurring in patients. Hospital patient safety must provide services that meet quality standards and ensure a sense of security and protection from the impact of services provided in order to realize the rights of the community to quality and safe services. This study aims to determine the Overview of Preparation for Patient Safety Implementation in the IBS Room. This study uses quantitative observation method with descriptive deSign in this study, using total sampling with a sample of 32 respondents, Surgical safety checklistobservation sheet, and data analysis using univariate analysis. The results of this study were obtained in age characteristics, most of them had an age range of> 39 years as many as 18 respondents (56.3%). In gender, 23 respondents (71.9%) were male. In the length of work, 20 respondents (62.5%) worked for a long time. In the implementation of the Surgical safety checklist, the Sign inphase was completed by 24 respondents (75.0%), the Time out phase was incomplete as many as 19 respondents (59.4%), the Sign out phase was incomplete as many as 18 respondents (56.3%).